Legitimize the Torrance test for creative thinking in performance and movement in children from (3 - 6) years in the Kingdom of Bahrain - Faraj, Sarah Shukri (Journal of Educational and Psychological Sciences, 2018)
The study aimed at legitimizing Torrance Thinking Creatively in Action and Movement for children aged 3-6 years in the Kingdom of Bahrain to be used as a tool for the detection of creative children. The study used the descriptive approach. Torrance test for creative thinking in performance and movement, the school readiness test, and the list of diagnosing gifted children for kindergarten and kindergarten as a means of collecting information, and applied to a sample of 160 randomly selected children in kindergarten for the academic year 2012/2013. The results showed that the TCAM test has a high level of honesty and consistency, which is a good test for the detection of creative children, and the results showed that there are no individual differences depending on the gender variable, Based on the results of the study, the criteria for the performance of the study members were extracted in the Bahraini environment. The criteria table was extracted according to the age group (3-6) years, in line with the Bahraini environment, in addition to a set of recommendations to develop the skills of creative thinking and attention to talents in the Kingdom of Bahrain.